THE IMPACT OF WORK FAMILY CONFLICT AND BURNOUT ON EMPLOYEE PERFORMANCE: MEDIATION OF ORGANIZATIONAL COMMITMENT - Safitri, Rini; Saputra, Ega (JURNAL DIMENSI, 2023)
This research aims to find out how work family conflict and burnout influence employee performance and also analyze the role of organizational commitment in mediating work family conflict on employee performance in hospitals. The type of research used is quantitative research with an explanatory research approach. The sample in this study was taken using a saturated sampling technique. The research results show that work family conflict and burnout have a significant effect on employee performance. Refers to the work family conflict variable with the highest indicator of time based conflict, which is the time needed to carry out one demand which can come from work or from the family which can reduce the time to carry out other demands. Organizational commitment also has a significant effect on employee performance, but does not mediate work family conflict on employee performance. These results prove that when an employee experiences a clash of roles, where the work role interferes with his role in the family and vice versa, the role in the family interferes with his role at work.